Biopolitics, imaginaries and tensions in the urban space : a decolonial critique of the discourse of inclusion in the city of San José, Costa Rica - Fournier Pereira, Mar 1985- (2022)
Discourses of inclusion have gained special importance in Costa Rican politics. Political parties promise inclusion, NGOs compete for international cooperation funds to develop projects along these lines, collectives demand inclusion, entrepreneurs and corporations offer inclusive commodities, spaces and experiences. However, when analyzing these discourses and practices, the notion of inclusion seems, paradoxically, too lax and at the same restricted to a small sector of beneficiaries. This thesis seeks to analyze, from a decolonial perspective, these dominant discourses and practices of inclusion in the city, as well as the narratives of people who inhabit the city. I also seek to elucidate the ways in which biopolitics flows through discourses of inclusion, generating new ways to regulate populations. In this sense, in this work, inclusion discourses and practices are understood as both cultural and material processes. I pursue the following hypothesis: (1) that both conservative and progressive projects of inclusion in San José, share the rhetoric of "rescue", which implies the intervention on bodies and spaces, wrought by social imaginaries on national identity, and therefore, (2) that the notion of inclusion in Costa Rica reproduces the coloniality of power. This approach is based on Christina Hanhardt's provocation to think of the city as "a critical nexus for analyzing how politics, policies and property have indelibly shaped LGBT social movements, in particular in response to violence" (Hanhardt, p.11). I think of the city of San José as a critical nexus for analyzing how biopolitics and national imaginaries have shaped social movements for inclusion (including LGBTIQ+). In dialogue with city dwellers who are left out of inclusive policies (trans* asylum seekers, queer people with disabilities, unhoused trans* people, sex workers, among others), I analyze the biopolitical and necropolitical practices that are reproduced in a variety...